A multi reaction kinetic model to describe the enzymatic transesterification reaction of jatropha oil using a fermented solid containing lipases - Diana D. Alcalá-Galiano-Morell; Luis B. Ramos-Sánchez; Patrick Fickers; Evelyn Romero-Borbón; Néstor D. Ortega-de la Rosa; Jesús Córdova (Carbon Resources Conversion, 2025)
The advancement of more precise tools for sustainable process design in enzymatic biodiesel synthesis from renewable sources is crucial. Kinetics of solvent-free transesterification reactions were conducted across a temperature spectrum from 30 °C to 60 °C, utilizing Jatropha curcas oil (TG) and ethanol as substrates, alongside a fermented solid by Rhizopus homothallicus as the biocatalyst. The dynamics of chemical species concentrations were monitored through High-performance Thin-Layer Chromatography. Maximum productivities were achieved at 35 °C and 60 °C for biodiesel (293.24 and 299.02 g kg biocat−1 h−1, respectively), at 40 °C for diglycerides (1018.36 g kg biocat−1 h−1), and at 35 °C for monoglycerides (560.75 g kg biocat−1 h−1). Maximum yields were determined at 30 °C for fatty acid ethyl esters (0.56 g gTG−1), and at 40 °C for diglycerides (0.53 g gTG−1) and monoglycerides (0.30 g gTG−1). Based on the experimental findings, a kinetic model was formulated encompassing three reversible transesterification reactions. Individual reactions were structured following classical biochemical kinetics, inclusive of ethanol inhibition. Model fitting was executed through non-linear multivariable regression techniques, with the minimum of the average coefficient of variation of the residuals (ACVR) serving as the objective function. The resulting fit of the kinetic model to the experimental data proved satisfactory, with an ACVR of less than 5 % across all instances. Notably, the maximum biodiesel productivity, obtained in this work, represented the highest value, compared to other related studies, using a fermented solid as a biocatalyst.